2018
DOI: 10.1002/anie.201713179
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium(I)‐Catalyzed Carboacylation/Aromatization Cascade Initiated by Regioselective C−C Activation of Benzocyclobutenones

Abstract: Described here is the first example of a rhodium-catalyzed carboacylation/aromatization cascade of a C=O bond by C-C activation. In this transformation, a reactive rhodaindanone complex is regioselectively generated and adds across a C=O bond with subsequent elimination, thus providing a unique strategy to access a multisubstituted benzofuran scaffold. A diverse range of benzofuran analogues were obtained in good yields. Mechanistic studies show a tricyclic lactone was a viable intermediate. Application of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
22
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 56 publications
(22 citation statements)
references
References 62 publications
0
22
0
Order By: Relevance
“…[7] To our delight, 2a was successfully isolated in 10 % yield. [11] An optimization of solvents revealed that ethereal solvents are preferred (entries [10][11][12][13][14], whereas DCE drastically limited conversion to 20 %and less than 10 %yield upon isolation. Several cationic rhodium pre-catalysts were screened and both conversions and yields were dramatically increased (entries 2-4).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…[7] To our delight, 2a was successfully isolated in 10 % yield. [11] An optimization of solvents revealed that ethereal solvents are preferred (entries [10][11][12][13][14], whereas DCE drastically limited conversion to 20 %and less than 10 %yield upon isolation. Several cationic rhodium pre-catalysts were screened and both conversions and yields were dramatically increased (entries 2-4).…”
mentioning
confidence: 99%
“…Heteroaryl-bearing ketone substrates were also found to be suitable substrates (entries [10][11][12][13]. Sterically hindered ortho-substituted phenyl ketones 1h and 1i were prepared and found to undergo the cascade transformation with even better efficiency, thus providing 2h and 2i, respectively,a nd in 90 %y ields (entries 8a nd 9).…”
mentioning
confidence: 99%
See 3 more Smart Citations